The complex relationship between intrinsic and extrinsic rewards - Gov, Orni (Economics and Business Review, 2015)
This study aimed to determine the relationship between the two main components of the organizational rewards system; intrinsic and extrinsic rewards. Pay satisfaction was chosen to represent the extrinsic rewards whilst the Thomas et al. four intrinsic rewards represented the intrinsic rewards. A total of one hundred and fifty six self-administered questionnaires were collected from Israeli employees. Analysis using Pearson correlation indicated that there is no relationship between the two types of rewards. However, a regression analysis demonstrated that employees with temporary status, and outsourcers’ employees, are experiencing less pay satisfaction than organizations’ directly-employed staff. Another regression analysis established that a sense of choice predicted a positive correlation with pay satisfaction whilst a sense of competence predicted a negative correlation. Based on the findings it can be concluded that there is a downside to an organization’s decision to reward  employees by empowering and giving them autonomy. The empowerment process might increase the employees’ sense of competence, which may lead to a decrease in pay satisfaction.